"TWO IN ONE": Transnational Inheritance and the Remaking of the Sinasite Houses as Shared Heritage Monuments. (9th March 2022) - Stuckey, Leigh
ABSTRACT : This article examines debates between Greeks and Turks about how to preserve the architectural heritage left behind by the Greek Orthodox population exiled from Sinasos in the 1923 Greek‐Turkish Compulsory Population Exchange. The restoration of Sinasos as a kind of residential and commercial open‐air museum, through the transformation of ancestral homes into hotels, engendered new cooperative and competitive relationships between Greeks and Turks with legitimate claims to the site. Greeks and Turks are typically portrayed as antagonistic, but understanding the historic properties as a form of inheritance much like the estates fundamental to "house societies" described by Claude Lévi‐Strauss reveals a transnational community with shared concerns around memory, heritage preservation, transnational identity formation, and touristic enterprise. [heritage, inheritance, house, memory, Turkey]